A novel splice site mutation in a Becker muscular dystrophy patient. Issue 4 (April 1996) - Bartolo, C; Papp, A C; Snyder, P J; Sedra, M S; Burghes, A H; Hall, C D; Mendell, J R; Prior, T W
Abstract : A Becker muscular dystrophy patient was found to have a single base substitution at the 5' end of intron 54. This single base substitution disrupts the invariant GT dinucleotide within the 5' donor splice site and was shown to cause an out of frame deletion of exon 54 during mRNA processing. This is predicted to produce a truncated dystrophin protein which is more consistent with a DMD phenotype. However, small quantities of normal mRNA are also transcribed and these are sufficient to produce a reduced amount of normal molecular weight dystrophin and give rise to a milder BMD phenotype. This indicates that a single base substitution at an invariant dinucleotide of the splice site consensus sequence may still allow read through of the message and allow the production of some normal protein. This shows that there are a greater number of possible intronic mutations that can lead to a mild phenotype and it also underlines the importance of performing cDNA analysis when screening for small gene alterations in the BMD patient population.